2003
DOI: 10.1016/s0009-9236(03)90491-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of IV Pantoprazole in Pediatric Patients

Abstract: Clinical Pharmacology & Therapeutics (2003) 73, P37–P37; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
2
6
1
Order By: Relevance
“…To date, studies of PPIs conducted in pediatric populations have not been able to demonstrate a statistically significant correlation between age and PK parameters. [6][7][8][9][10]34 A similar conclusion was obtained from the current data when the PK parameters for pantoprazole (including λz, which is not influenced by absorption) from CYP2C19 extensive metabolizers were examined in association with age. The apparent age-independence of pantoprazole PK is further illustrated by similarity in pantoprazole plasma CL after IV administration in children ranging in age from 2 to 16 years and data generated from healthy adults (data on file, Byk-Gulden (Altanta) Protocol No.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To date, studies of PPIs conducted in pediatric populations have not been able to demonstrate a statistically significant correlation between age and PK parameters. [6][7][8][9][10]34 A similar conclusion was obtained from the current data when the PK parameters for pantoprazole (including λz, which is not influenced by absorption) from CYP2C19 extensive metabolizers were examined in association with age. The apparent age-independence of pantoprazole PK is further illustrated by similarity in pantoprazole plasma CL after IV administration in children ranging in age from 2 to 16 years and data generated from healthy adults (data on file, Byk-Gulden (Altanta) Protocol No.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast to pantoprazole, the PK of omeprazole and lansoprazole have been well characterized in children older than 2 years of age with acid‐related diseases. Available PK data for omeprazole, 8 pantoprazole, 9 and lansoprazole 10 suggest a similarity between adult and pediatric data that supports the use of exposure‐response correlates established for adults to guide the dosing of PPIs in pediatric patients requiring acid‐suppression therapy 6 …”
mentioning
confidence: 85%
“…One included 14 paediatric intensive care patients between 2 and 16 years of age receiving i.v. pantoprazole [22]. The only kinetic parameter reported in the study was the mean t 1/2 , which was shorter than the median t 1/2 observed in our patients (1.1 ± 0.5 h compared with 2.0 h (0.7–11.8 h)).…”
Section: Discussioncontrasting
confidence: 74%
“…To date, two paediatric trials have studied the pharmacokinetics of pantoprazole [22, 23]. One included 14 paediatric intensive care patients between 2 and 16 years of age receiving i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation